Land use options for staying within the Planetary Boundaries – Synergies and trade-offs between global and local sustainability goals. (March 2018) - Heck, Vera; Hoff, Holger; Wirsenius, Stefan; Meyer, Carsten; Kreft, Holger
Highlights: Large global potentials for carbon sequestration and biodiversity risk reduction. Agricultural productivity increases necessary for safeguarding future food supply. Trade-offs and synergies between global and local-level sustainability goals. Boreal and tropical zones are hot-spot regions for carbon-biodiversity trade-offs. Abstract: In this paper we develop and assess alternative global land use patterns, guided by the Planetary Boundaries framework, to quantify land use opportunities for staying within the safe environmental operating space. Through a simulation based multi-criteria land use optimisation procedure, we determine the potential upper bounds of improved terrestrial carbon storage and of biodiversity conservation, while also meeting the Planetary Boundaries of land and water use and ensuring improved food supply for a population of 9 billion people. We present alternative global land use scenarios that could simultaneously yield better outcomes on all of these goals, in particular if substantial increases in agricultural productivity are realised. Terrestrial carbon sequestration potentials reach 98 GtC, whereas the potential reduction of the risk to biodiversity is 53%. Furthermore, we analyse the potential synergies and trade-offs of these global land use scenarios with national- and local-level environmental and developmental goals such as those specified in the SDGs, e.g. related to nature conservation, afforestation, bioenergy, employment and equity. This model-based information on synergies and trade-offs between different sustainability goals at different scales can be used in scientific assessments of transformation pathways, in policy making, in support of improved horizontal and vertical policy coherence and multi-level institutional solutions, as well as in SDG implementation, sustainable production and consumption (SDG 12) and global partnership mechanisms (SDG 17).